MODERN INTERPRETATION OF FORMING A PERSON’S MORAL AND VOLITIONAL QUALITIES ON THE BASIS OF MOVEMENT GAMES (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article analyzes the theoretical and practical aspects of developing an individual’s moral and volitional qualities through movement-based games. Based on modern pedagogical approaches, the educational potential of such games is revealed, and their role in personal development is scientifically substantiated. Furthermore, the study examines the mechanisms for forming social behavior, volitional stability, and moral norms in preschool and early school-age children.